Hypoxia regulates proliferation of acute myeloid leukemia and sensitivity against chemotherapy. Issue 7 (July 2015) - Drolle, Heidrun; Wagner, Michaela; Vasold, Jochen; Kütt, Alexander; Deniffel, Christian; Sotlar, Karl; Sironi, Silvia; Herold, Tobias; Rieger, Christina; Fiegl, Michael
Highlights Hypoxia is present in the bone marrow but levels are not altered in AML. This physiological hypoxia ranges from 1 to 6% O2. Hypoxia leads to decreased proliferation and chemosensitivity of AML blasts. Relevant mechanisms comprise regulation of p27 and antiapoptotic proteins. PI3Kinase seems to be involved and inhibition could be therapeutically exploited.